The Role of the Arabic Language in Enhancing Intellectual Intelligence of Students at UIN Maulana Malik Ibrahim Malang - Nevin Nismah, Zakiah Muftie Daradjah, Ihsan Muhammad Saefullah Syaiful Mustofa (Universitas Trunodjoyo Madura, 2024)
Intellectual Intelligence is the thinking ability possessed by every individual where this intelligence can help a person to be able to adapt to the environment around them through thinking about various things through metacognitive processes. One area of knowledge that is predicted to have an influence on increasing intellectual intelligence is Arabic, where Arabic is the language of the Koran which is rich in vocabulary, language structure and beautiful language style. However, this has not been proven, especially for UIN Maulana Malik Ibrahim Malang students. For this reason, researchers want to conduct research on the role of Arabic in increasing the intellectual intelligence of students at UIN Maulana Malik Ibrahim Malang. The aim of this research is to determine the role of Arabic in increasing students' intellectual intelligence. The research method used is descriptive qualitative with data collection techniques through observation and documentation with primary data sources, namely UIN Maulana Malik Ibrahim Malang Postgraduate students, class F in 2023. The data collected was then analyzed in depth to determine the research results. The research results show that Arabic can play a role in improving students' intellectual intelligence through three aspects, namely dalil, mahfudzot, work, and learning outcomes. Propositions and mahfudzot include verses from the Koran, Hadith of the Prophet, and sayings of the Shafi'i Faith. Works in the form of Masrohiyyah and calligraphy. Meanwhile, student learning outcomes include cumulative achievement index (GPA), general knowledge scores, and competition achievements at the Arabian Peninsula Festival